Modelo Prolab: Sumaq Pacha, una solución sostenible para mejorar la calidad de vida de los habitantes de zonas de friaje, a través de la fabricación de ropa Interior térmica - Bojorquez Velis, Josue Eduardo (2024)
The study aims to develop a sustainable business solution that addresses a growing social issue, intensified by global climate change. In Peru, poverty rates have risen significantly due to the pandemic, while the Andean regions, located above 3,000 meters above sea level, suffer from extreme cold or frost for much of the year. This harsh climate severely impacts the daily lives and health of the people living in these highland communities. “Sumaq Pacha” is a company created to tackle this issue by producing high-quality thermal underwear using a combination of new and recycled fabrics. These garments are designed to protect against extreme cold, offering a functional and affordable solution. The project also has a strong social component, creating local employment by involving residents of highland areas in the manufacturing process, thus improving their economic conditions. The initial investment required for this solution is 383,510.74 , with a Net Present Value (NPV) of 3,785,895.96 and a Modified Internal Rate of Return (MIRR) of 84.2%. “Sumaq Pacha” is not only an economic and social solution but also a sustainable one, focusing on reducing water consumption and textile waste. By promoting the use of recycled materials, the company aims to contribute to a more responsible and environmentally friendly textile industry while improving the quality of life for people in the Andean highlands.